The Effect of Principal Instructional Leadership and School Climate on ES Teacher Performance - Yolanda, Septiara; Awam, Rafizah; Gistituati, Nurhizrah (International Journal of Educational Dynamics, 2023)
Many aspects can affect teacher performance. However, on this occasion, the purpose of writing this research article was to see how the Effect of Principal Learning Leadership and School Climate on Elementary School Teacher Performance. This type of research is quantitative research. The research location is Elementary School 15 Kampung Baru. The research population was all teachers who taught at Elementary School 15 Kampuang Baru, totaling 17 people. All populations were sampled using the total sampling technique. A questionnaire using a Likert scale model that has been evaluated for validity and reliability is used to collect data. The data obtained were analyzed using SPSS version 25 and simple and multiple linear regression tests. The results showed that: 1) the instructional leadership of the principal had a significant effect on the performance of elementary school teachers by 30.2%; 2) school climate has a significant effect on the performance of elementary school teachers by 44.1%; and 3) the instructional leadership of the principal and the combined school climate have a significant effect on the performance of elementary school teachers by 50.9%. Other variables not examined affect 49.1%.